A CLS-based survivable and energy-saving WDM-PON architecture - Zhong, Wende (2013)
We propose and demonstrate an improved survivable and energy-saving WDM-PON with colorless ONUs. It incorporates both energy-saving and self-healing operations. A simple effective energy-saving scheme is proposed by including an energy-saving control unit in the OLT and a control unit at each ONU. The energy-saving scheme realizes both dozing and sleep (offline) modes, which greatly improves the energy-saving efficiency for WDM-PONs. An intelligent protection switching scheme is designed in the OLT, which can distinguish if an ONU is in dozing/sleep (offline) state or a fiber is faulty. Moreover, by monitoring the optical power of each channel on both working and protection paths, the OLT can know the connection status of every fiber path, thus facilitating an effective protection switching and a faster failure recovery. The improved WDM-PON architecture not only significantly reduces energy consumption, but also performs self-healing operation in practical operation scenarios. The scheme feasibility is experimentally verified with 10 Gbit/s downstream and 1.25 Gbit/s upstream transmissions. We also examine the energy-saving efficiency of our proposed energy-saving scheme by simulation, which reveals that energy saving mainly arises from the dozing mode, not from the sleep mode when the ONU is in the online state.